ALTEX 2007
DOI: 10.14573/altex.2007.3.153
|View full text |Cite
|
Sign up to set email alerts
|

VirtualToxLab ~ in silica prediction of the toxic potential of drugs and environmental chemicals: evaluation status and Internet access protocol

Abstract: SummaryWe present a receptor-modeling concept based on multidimensional QSAR (mQSAR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Another technique known as the pseudoreceptor technique (Tanrikulu and Schneider, 2008) uses pharmacophore mapping-like overlaying techniques for a collection of ligands that bind to the same binding site to establish a virtual representation of the binding site's structure, which is then used as a template for docking and other structure-based vHTS. This approach has been used by VirtualToxLab (Vedani et al, 2007) for the creation of nuclear receptors and cytochrome P450 binding site models in ADMET prediction tools and by Tanrikulu et al (2009). in the modeling of the H4 receptor binding site subsequently used to identify novel active scaffolds .…”
Section: Discussionmentioning
confidence: 99%
“…Another technique known as the pseudoreceptor technique (Tanrikulu and Schneider, 2008) uses pharmacophore mapping-like overlaying techniques for a collection of ligands that bind to the same binding site to establish a virtual representation of the binding site's structure, which is then used as a template for docking and other structure-based vHTS. This approach has been used by VirtualToxLab (Vedani et al, 2007) for the creation of nuclear receptors and cytochrome P450 binding site models in ADMET prediction tools and by Tanrikulu et al (2009). in the modeling of the H4 receptor binding site subsequently used to identify novel active scaffolds .…”
Section: Discussionmentioning
confidence: 99%
“…A full assessment of their possible endocrine-disrupting effects is critical for individual PCBs and their metabolites; unfortunately, traditional toxicological studies are costly and time consuming. To meet the needs of contemporary toxicology, a growing number of in silico tools and quantitative structure-activity relationship (QSAR) models are being developed for surrogate use in evaluation of chemicals for which data are lacking [33][34][35][36][37][38][39][40][41][42]. Through these efforts, meaningful chemical structural features can be identified that will lead to the development of robust predictive models, and specific selection criteria for use of such models [38,39,[41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…typical examples come from protein modelling, such as models of the estrogen receptor or various P-450 enzymes, where crystal structures are used to model the fit of the test compound into the reactive site of the receptor and to determine the likelihood of its triggering a response. these models are typically three-dimensional, but notably there are also 4D-models, which accommodate the induced fit of the substance on the receptor (Vedani et al, 2007) or pseudo-receptor models (Vedani et al, 2005). In case of the latter, in the absence of a real receptor, available data on a training set of ligands are used to emulate a hypothetic receptor to then be applied to new, untested substances.…”
Section: Data Analysis Procedures (Dap) -Every Experiments Requiresmentioning
confidence: 99%